2022
DOI: 10.47162/rjme.63.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell density in the primary tumor predicts lymph node metastases in patients with breast cancer

Abstract: Breast cancer (BrCa) is the most frequent neoplastic disease in female, with high morbidity and mortality. Most of the researches were focused on tumor cells concerning their natural evolution, molecular profile, and potential response to therapy. Few and uncertain data are available about the tumor microenvironment and its impact on the progression of the disease. Mast cells (MCs) associated to BrCa have been reported many years ago, but their real and specific role in the biology of this disease remained elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Moreover, multifactorial COX regression analysis revealed that infiltration of CD8 + T cells and mast cells played a role as prognostic biomarkers of bladder cancer. Recent investigations have indicated that reducing the infiltration and activity of CD8 + T cells can promote resistance to immunotherapy in bladder cancer, 22 whereas mast cell density has been shown to predict lymph node metastasis in patients with breast cancer 23 . Interestingly, we observed a correlation between YARS1 expression and the degree of CD8 + T‐cell and mast cell infiltration.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, multifactorial COX regression analysis revealed that infiltration of CD8 + T cells and mast cells played a role as prognostic biomarkers of bladder cancer. Recent investigations have indicated that reducing the infiltration and activity of CD8 + T cells can promote resistance to immunotherapy in bladder cancer, 22 whereas mast cell density has been shown to predict lymph node metastasis in patients with breast cancer 23 . Interestingly, we observed a correlation between YARS1 expression and the degree of CD8 + T‐cell and mast cell infiltration.…”
Section: Discussionmentioning
confidence: 52%
“…Recent investigations have indicated that reducing the infiltration and activity of CD8 + T cells can promote resistance to immunotherapy in bladder cancer, 22 whereas mast cell density has been shown to predict lymph node metastasis in patients with breast cancer. 23 Interestingly, we observed a correlation between YARS1 expression and the degree of CD8 + T‐cell and mast cell infiltration. Additionally, patients with high YARS1 expression displayed a poor response to immune checkpoint inhibitor therapy.…”
Section: Discussionmentioning
confidence: 67%
“…MCs, recognized for their involvement in allergic reactions and various physiological processes, including angiogenesis, wound healing, fibrosis, and immune regulation, have also garnered attention in the context of diseases, including tumors (6). Over a century ago, Ehrlich and Westphal reported the presence of MCs in human tumors for the first time (7). Extensive evidence suggests that MCs accumulating around tumors can either promote or inhibit tumor growth, contingent on local stromal conditions and the stage of tumorigenesis (8).…”
mentioning
confidence: 99%